Relationship between gliadin peptide structure and their effect on the fetal chick duodenum - Kocna, P; Mothes, T; Krchnák, V; Fric, P (Zeitschrift fur Lebensmittel-Untersuchung und -Forschung, 1991)
The tendency to form a beta-turn in alpha-gliadin was estimated using the B-cell determinant prediction program based on the Chou and Fasman probability of beta-turn formation. Six sequences possessing a high probability of beta-turn formation were found. A statistically high agreement was found between these six sequences and three areas in alpha-gliadin with the occurrence of Pro-Ser-Gln-Gln sequence which has recently been considered responsible for toxicity in coeliac disease. By means of solid-phase synthesis seven peptides were obtained covering the above-mentioned regions. Their toxicity was tested using the fetal chick duodenum. The results support the suggestion that peptides containing the sequences Pro-Ser-Gln-Gln and Gln-Gln-Gln-Pro may be involved in the pathogenesis of coeliac disease.
Keywords: Molecular Sequence Data; Gliadin; Animals; Duodenum; sekvence aminokyselin; molekulární sekvence - údaje; kuřecí embryo; zvířata; Amino Acid Sequence; Celiac Disease; Chick Embryo; celiakie; gliadin; duodenum